A unified pore-network algorithm for dynamic two-phase flow. (September 2016) - Sheng, Qiang; Thompson, Karsten
Highlights: Both transient and steady-state flow modeled using a novel network approach. Fractional flow used as novel boundary condition for the network modeling. A semi-implicit algorithm developed for improved speeds and numerical stability. Quantified limitations of periodic BCs for hysteretic and history-dependent behavior. Simulated steady-state relative permeability test using dynamic network model. Abstract: This paper describes recent work on image-based network modeling of multiphase flow. The algorithm expands the range of flow scenarios and boundary conditions that can be implemented using dynamic network modeling, the most significant advance being the ability to model simultaneous injection of immiscible fluids under either transient or steady-state conditions using non-periodic domains. Pore-scale saturation distributions are solved rigorously from two-phase mass conservation equations simultaneously within each pore. Results show that simulations using a periodic network fail to track saturation history because periodic domains limit how the bulk saturation can evolve over time. In contrast, simulations using a non-periodic network with fractional flow as the boundary condition can account for behavior associated with both hysteresis and saturation history, and can capture phenomena such as the long pressure and saturation tails that are observed during dynamic drainage processes. Results include a sensitivity analysis of relative permeability to different model variables, which may provide insight into mechanisms for a variety of transient, viscous dominated flow processes.